Willardian Spiritual Formation, Novel Spiritual Disciplines, and Basketball: A Case Study - Roberts, Matthew (Journal of spiritual formation & soul care, 2020)
Athletic participation provides a unique forum for the practice of spiritual disciplines. Central to Dallas Willard’s robust theory of spiritual formation is the critical role the body plays in effectively engaging in spiritual disciplines and thereby cultivating Christlikeness. I outline the central themes of Willard’s theology and philosophy of spiritual disciplines, with particular attention to how they bear on athletic participation. I distinguish between classical and novel spiritual disciplines and show how the latter are usefully appropriated towards the ordinary activities of daily life, and particularly towards the arena of athletics. Using basketball as a case study, I show in detail how this activity can be fruitfully reappropriated as a set of novel spiritual disciplines.